Comparison of postoperative outcomes between different dissection techniques during laparoscopic cholecystectomy in rabbits: randomized study - Vera, María Camila Maldonado [UNESP]; Wittmaack, Monica Carolina Nery [UNESP]; Conceição, Maria Eduarda Bastos Andrade Moutinho [UNESP]; Faccini, Rachel Inamassu [UNESP]; Sembenelli, Guilherme [UNESP]; Montanhim, Gabriel Luiz [UNESP]; de Menezes, Mareliza Possa [UNESP]; Ido, Cléber Kazuo [UNESP]; Aires, Luiz Paulo Nogueira [UNESP]; Carra, Gabriel João Unger [UNESP]; Moraes, Paola Castro [UNESP] (FapUNIFESP (SciELO), 2024)
Purpose: Laparoscopic cholecystectomy (LC) is the gold standard for the treatment of gallbladder (GB) disease in small animals. The aims of this study were to investigate and compare the effect of different types of dissectors during LC in rabbits; electrothermal bipolar vessel sealing device (EBVS-LigaSure) and standard electrosurgical dissection (bipolar Maryland) for dissection of the GB in LC, correlating liver function tests (LFTs) in pre and postoperative periods (days 0, 3, 7, 15); macroscopic checking 15 days after surgery through necropsy; histopathological, bacteriological through bacterial growth by culture and intraoperative complications. Methods: Twenty rabbits were used, group (n = 10) using EBVS for GB dissection and cystic duct seal (GLL), and group (n = 10) using bipolar dissecting forceps and EVBS for cystic duct seal (GLE). Results: A higher concentration of alkaline phosphatase was observed on GLL 15 days after surgery when compared to GLE. In addition, GLE resulted in a higher concentration of alanine aminotransferase at three days when compared to GLL. Conclusion: In LC no significant statistical differences were found between EBVS and bipolar Maryland; both devices are equally safe and effective in LC. Further studies are required to evaluate the effectiveness of these devices in animals with gallbladder pathologies. Therefore, clinical studies are necessary.
Keywords: Adhesions; Cholecystectomy; Electrosurgery; Laparoscopy; Rabbits